Identity Construction of English Language Education Department Students - Rika Mutiara (Universitas Islam Negeri (UIN) Mataram, 2020)
Language, identity, and community are interrelated elements. One’s identity was developed by his language use. The languages he uses depend on the community he belongs to. Constructing an identity is a lifetime process that is influenced by several factors. The present study deals with the identities of English Department students. It explores students’ identities construction. It began with an investigation of how they view their identities by analyzing family backgrounds and neighborhoods. Furthermore, it investigated how studying in the English Language Education Department contributes to identity construction as they become members of a new community. The present study applied a narrative inquiry by analyzing students’ self-reflections and conducting interviews. The students were exposed to local languages and Indonesian when they grew up. They studied English in primary school. Some of them use the local languages to talk to their families. The others only understand them but they are not able to speak the languages. The influence of environment and neighborhood makes them identify themselves as Jakartan even though their parents came from some regions in Java and Sumatera. They, moreover, do not accept all local values of their current environment. Cultural origins of the parents also play a role in students’ identity construction. The status of English Department students encourages them to use English with classmates. In addition, they use English to broaden their social relationship such as making friends with foreigners and getting exposed to the international community. It gives a contribution to their identity construction.